Can India grow without Bharat? "columnspeak" - Acharya, Shankar N. (New Delhi Academic Foundation, 2007)
Excerpts of author's columns from the Business standard focussed on India economic policy related issues.
Keywords: India -- Economic policy -- 1991-.